PENGARUH PERMAINAN GOBAK SODOR TERHADAP KECERDASAN INTERPERSONAL SISWA KELAS V DI SD N GEDONGKUNING, KOTAGEDE, KOTA YOGYAKARTA - Sri Mawarningsih; Ahmad Agung Yuwono Putro (STKIP Subang, 2026)
This study aimed to determine the differences in students' interpersonal intelligence after being given a game of gobak sodor. The study was conducted at Gedongkuning Elementary School and involved 52 fifth-grade students, divided into two groups: an experimental group and a control group. The method used in this study was an experimental one. Data collection was conducted through observation and questionnaires, while data analysis employed a quantitative approach. The experimental group was given the game of gobak sodor, while the control group did not receive any treatment. The results showed a difference in interpersonal intelligence between the two groups. The average score in the experimental group reached 85.18%, with a highest score of 72 and a lowest of 54. Meanwhile, the control group achieved an average score of 81.33%, with a highest score of 71 and a lowest of 49. Statistical analysis using an independent sample t-test showed a significance value (Sig. 2-tailed) of 0.034, which is less than 0.05. This indicates a significant effect of the game of gobak sodor on improving students' interpersonal intelligence. Thus, it can be concluded that the game of gobak sodor is effective in improving the interpersonal intelligence of fifth-grade elementary school students. This game is not only fun but also trains students' cooperation, communication, and social skills in interacting with peers.